Developing an information exchange scheme concerning value for money assessment in Public-Private Partnerships. (September 2019) - Guoqian Ren,; Li, Haijiang; Ding, Rui; Zhang, Jisong; Boje, Calin; Zhang, Weishuai
Abstract: Value for money (VFM) as the procurement justification assessment approach in Public-Private Partnerships (PPP) essentially justify the overall project feasibility in both qualitative and quantitative ways. However, the performance measurement in VFM still lacks automation and information exchange schema. Concerning the project management domain within the Architectural–Engineering–Construction/Facility Management (AEC/FM) sectors, Building Information Modelling (BIM) is emerging as a potential solution for owners to automate the process of value for money assessment. Based on the published performance structure in PPP procurement, This paper develops a novel schema to formalize the information exchange needed to support data extraction and performance measurement. The schema was achieved by referencing the standardised Information Delivery Manual (IDM), which specifies the required information exchanges. This proposed method facilitates the automatic VFM assessment thus benefit the PPP procurement. Software development and case study model are presented towards the validation of the schema and methods employed. Highlights: Break down the contents of Value for money assessment and propose the BIM-based information exchange scheme. Using ontology to represent the exchange scheme that can be delivered to software vendors. Develop a Tool for data extraction and indicate the technical feasibility based on the initial design.